General Study of Educational Organization Commitment - El-Yunusi, Melikai Jihan; Maimun, Agus; Kawakib, Akhmad Nurul; El-Warfali, Sulaiman (Al-Hayat: Journal of Islamic Education, 2025)
Organisational commitment is a bond between individuals and organisations, reflecting a sense of belonging and support for the organisation's values and goals. The main problem in this study is the lack of consensus in defining the construct of organisational commitment. The measure of commitment that does not always match the definition applied makes it challenging to synthesise research results related to organisational commitment. This study aims to understand the concept of organisational commitment and the factors that influence the formation of this commitment. This study uses a qualitative literature study approach to analyse books, articles, and journals related to organisational commitment in education. Data were collected by selecting relevant literature and tested for validity with source triangulation. Data analysis was carried out descriptively and interpretively, followed by writing and revising the manuscript until the final. The study's results identified three dimensions of organisational commitment: affective, continuance, and normative. Affective commitment encourages emotional attachment and innovation, while continuance commitment focuses on high output costs and can cause frustration. Normative commitment increases participation and performance. This study also identified four main approaches to understanding organisational commitment factors: attitudinal, behavioural, multidimensional, and normative. This commitment affects individual awareness, rules, communication, facilities, and work characteristics. In education, organisational commitment is negatively related to turnover and affects organisational performance and sustainability. This study enriches the understanding of organisational commitment in education, highlighting the affective, continuance, and normative dimensions influencing engagement and innovation. The limitations of this study include the limited context of education and quantitative measurement because it may ignore psychological nuances. Further research can explore the impact of commitment dimensions on performance in various sectors and use a qualitative approach to explore individual factors and social contexts that influence organisational sustainability.